2016
DOI: 10.1021/acs.molpharmaceut.6b00839
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticle Based Contrast Agents for Magnetic Resonance Imaging

Abstract: Magnetic iron oxide nanoparticles (MIONs) have attracted enormous attention due to their wide applications, including for magnetic separation, for magnetic hyperthermia, and as contrast agents for magnetic resonance imaging (MRI). This review article introduces the methods of synthesizing MIONs, and their application as MRI contrast agents. Currently, many methods have been reported for the synthesis of MIONs. Herein, we only focus on the liquid-based synthesis methods including aqueous phase methods and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
232
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(235 citation statements)
references
References 80 publications
1
232
0
2
Order By: Relevance
“…9 T 1 or spin–lattice contrast may be enhanced through the use of paramagnetic centers such as gadolinium 10,11 or manganese ions, 12,13 whereas iron oxide-based nanosystems are often used for T 2 -weighted 14-16 or spin–spin imaging. Unlike other molecular imaging agents, these nanoparticles are not directly imaged in the resulting MRI image; in fact, the metal ions perturb the magnetic properties of protons around them, which are the actual target of a traditional MRI scan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 T 1 or spin–lattice contrast may be enhanced through the use of paramagnetic centers such as gadolinium 10,11 or manganese ions, 12,13 whereas iron oxide-based nanosystems are often used for T 2 -weighted 14-16 or spin–spin imaging. Unlike other molecular imaging agents, these nanoparticles are not directly imaged in the resulting MRI image; in fact, the metal ions perturb the magnetic properties of protons around them, which are the actual target of a traditional MRI scan.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of this process is much greater than initially expected, calling for broad expertise in a multidisciplinary manner through chemistry, physics, biology, and engineering. The goal of this review is not to comprehensively summarize nanoparticulate CAs for MRI that have been reported so far, 26 as there are many reviews available that list the major types of NPs as CAs (Gd 3+ -based T 1 CAs, 11,27 magnetic T 2 CAs, 14,15,28-30 and dual- T 1 / T 2 CAs 9,31 ) or summarize a special application of CAs ( e.g ., bioresponsive CAs, 32-34 and multimodal CAs 24 ). Instead, this review intends to comprehensively discuss the main rules and mechanisms of nanoparticulate CAs, key factors influencing the relaxation of CAs, and innovative strategies to engineer CAs with high relaxivity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research/review articles have discussed the development of nanoparticles in biomedical applications [1114]. Among these nanoparticles, superparamagnetic iron oxide nanoparticles (SPIONs) are not only approved by the Food and Drug Administration (FDA) but are also widely used as contrast agents for bowel, liver, and spleen imaging due to inherent biocompatibility and unique magnetic characteristics.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Non-hydrolytic methods are used to produce high crystalline iron oxide nanoparticles with uniform size distribution. Since this review’s focus is to delineate the application of magnetic nanoparticles in prostate cancer, we have not considered the extensive preparative synthetic procedures of magnetic nanoparticles, but this information can be found elsewhere [1114]. Therefore, in this section, we will focus more on the creation of stable magnetic nanoparticle composition (regulating size and shape of magnetic nanoparticles) that is responsible for absorption, distribution, metabolism, and excretion (ADME).…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…[11][12][13] Superparamagnetic iron oxide nanoparticles (NPs), a kind of powerful T2 contrast agent, are commonly used as magnetic vectors for MRI. Compared with gadolinium-based MRI contrast agents, including Magnevist ® (Gd-DTPA; Bayer Schering Pharma, Berlin, Germany) and Multihance ® (Gd-BOPTA; Bracco Diagnostics Inc., Princeton, NJ, USA), 14,15 superparamagnetic iron oxide NPs have been intensively investigated as promising MRI probes because of their biocompatibility and safety profiles as well as suitable magnetic properties. [16][17][18] However, limitations such as low sensitivity have hindered the further application of MRI as the sole methodology in the diagnosis…”
Section: Introductionmentioning
confidence: 99%